2011
DOI: 10.1186/1475-2875-10-185
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the efficacy and tolerability of dihydroartemisinin - piperaquine - trimethoprim versus artemether - lumefantrine in the treatment of uncomplicated Plasmodium falciparum malaria in Cameroon, Ivory Coast and Senegal

Abstract: BackgroundThe ACT recommended by WHO is very effective and well-tolerated. However, these combinations need to be administered for three days, which may limit adherence to treatment.The combination of dihydroartemisinin - piperaquine phosphate - trimethoprim (Artecom®, Odypharm Ltd), which involves treatment over two days, appears to be a good alternative, particularly in malaria-endemic areas. This study intends to compare the efficacy and tolerability of the combination dihydroartemisinin - piperaquine phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…In adults in Thailand, the protective efficacy of DHAPQ was 98% when DHAPQ was administered monthly and 86% when it was administered bimonthly (11). Despite extensive clinical evaluation and use of DHAPQ in Southeast Asia (12,13) and Africa (14)(15)(16), few studies have addressed pharmacokinetics of PQ in children (17)(18)(19). However, one of these studies suggested that children are underdosed with current regimens (17), which was also supported by a recent meta-analysis (20).…”
mentioning
confidence: 86%
“…In adults in Thailand, the protective efficacy of DHAPQ was 98% when DHAPQ was administered monthly and 86% when it was administered bimonthly (11). Despite extensive clinical evaluation and use of DHAPQ in Southeast Asia (12,13) and Africa (14)(15)(16), few studies have addressed pharmacokinetics of PQ in children (17)(18)(19). However, one of these studies suggested that children are underdosed with current regimens (17), which was also supported by a recent meta-analysis (20).…”
mentioning
confidence: 86%
“…Combinations of MQ and artesunic acid with ciprofloxacin, which are experimentally active in vitro against P. falciparum-iRBCs, appear promising ). The derivatisation of the fluoroquinolone ciprofloxacin enhanced the in vitro activity and yielded compounds that were 10-100-fold more active than ciprofloxacin (Dubar et al 2009); chalcones combined with ART (Bhattacharya et al 2009) and pyronaridine combined with artesunate (AS) (Tshefu et al 2010) and dihydroartemisinin-piperaquine (Menan et al 2011) showed intense activity, with the latter exhibiting advantages over artemether-lumefantrine in human malaria.…”
Section: Drug Combinations and Hybrids Used In Antimalarial Chemothermentioning
confidence: 99%
“…The indicator for treatment success was adequate clinical and parasitological response (ACPR). ACPR was de ned as absence of parasitaemia by the end of treatment (days 14, 28, 42, 63) irrespective of axillary temperature without previously meeting any of the criteria for early treatment failure or late clinical failure or late parasitological failure (17)(18)(19)(20). The treatment success was de ned based on PCR genotyping according to current World Health Organisation (WHO) recommendation.…”
Section: Assessment Of Treatment Outcomesmentioning
confidence: 99%
“…A total of 39 studies from 16 records with the same or different ACTs ful lled the inclusion criteria and were included in this systematic review and meta-analysis with a total sample size of 3,747 participants that ranged from a minimum of 48 patients [22] to a maximum of 255 patients [30]. Treatment outcomes in all studies were evaluated by adopting clinical and parasitological criteria based on WHO guidelines [17][18][19][20].…”
Section: Qualitative Synthesismentioning
confidence: 99%